The Relationship between the Intrarenal Dopamine System and Intrarenal Renin-angiotensin System Depending on the Renal Function - Matsuyama, Takashi (Intern Med, 2018)
OBJECTIVE: The mechanisms underlying the intrarenal renin-angiotensin system (RAS) activation depend on the conditions of kidney diseases. In angiotensin II (AngII) infusion models, the circulating AngII is filtered into the renal tubular lumens, activating intrarenal RAS. However, in the chronic kidney disease (CKD) models, plasma angiotensinogen (AGT) is filtered into the tubular lumens because of glomerular injury, activating intrarenal RAS. The intrarenal dopamine system activation reduces intrarenal AGT expression and suppresses the intrarenal RAS activity in AngII infusion models. However, the relationship between the intrarenal dopamine system and intrarenal RAS has not been elucidated. Therefore, this study was conducted to determine that relationship in CKD patients. METHODS: We recruited 46 CKD patients (age: 51.1±20.0 years; 16 men; causes of CKD: chronic glomerulonephritis, 34; diabetic nephropathy, 2; nephrosclerosis, 4; and others, 6) not undergoing dialysis or taking RAS blockers. The urinary dopamine (U-DOPA) level, an indicator of intrarenal dopamine activity, and the urinary AGT (U-AGT) level, a surrogate marker of intrarenal RAS activity, were measured. RESULTS: As the CKD stages progressed, the U-DOPA levels decreased while the U-AGT levels increased. The U-DOPA levels were significantly and negatively correlated with the U-AGT levels but significantly and positively correlated with the estimated glomerular filtration rate (eGFR). A multiple regression analysis revealed that the U-DOPA levels were associated with the U-AGT levels after adjusting for age, sex, body mass index, and blood pressure (β=-0.38, p=0.045). However, no correlation was observed when eGFR was also adjusted (β=-0.17, p=0.29). CONCLUSION: The negative correlation between the intrarenal dopamine system and intrarenal RAS in CKD patients may be affected by the renal function.